Waking Up From "Conjecture" As Well As From "Dream": A Presentation of AIME - Latour, Bruno (Swiss Journal of Sociocultural Anthropology, 2015)
As every ethnographer knows, in addition to the many blunders every one of us commits in the course of our fieldwork, there exist also graver mistakes when we sense a mistaken regime of reality granted to an entity. It is at those moments, usually the most revealing in the course of our inquiries, when we try to repair broken relations by some innovative move to define the status of the contrasting realities that have been open to misinterpretation. During the last quarter century I have attempted, quite systematically, to increase the number of templates by which the so-called Moderns account for themselves; not, to be sure, in their official representation (they remain staunch adepts of the Object-Subject Operating System and will swear that they are obedient naturalists), but by looking for the many occasions where they express dissatisfaction with such an official view of themselves. What I think I have documented are the protestations by many different people that a skewed template is being used to account for the mode of existence of the agencies that are most attached to them.